The Effect of Gadget Management on Student’s Learning Motivation - Sajdah, Meilisa; Uyun, Muhammad; Isnaini, Muhammad; Defnaldi, Defnaldi (Graduate Program Magister Manajemen Pendidikan, 2023)
The primary goal of this study is to identify, describe, and analyze the impact of the management variable of the X1 device (gadget) and the variable of student learning motivation (Y). In order to determine the impact of gadgets on the learning motivation of class IX students at SMP Negeri 10 Kotabumi, this study employs quantitative research methods with 60 participants. A closed questionnaire with multiple choice answers was used to collect data. The research data collected was analyzed using descriptive analysis techniques. The findings revealed that the use of gadgets had a very strong influence on the learning motivation of class VII students of SMP Negeri 10 Kotabumi.